Fast Lithium Ion Conduction in Lithium Phosphidoaluminates. Issue 14 (7th January 2020) - Restle, Tassilo M. F.; Sedlmeier, Christian; Kirchhain, Holger; Klein, Wilhelm; Raudaschl‐Sieber, Gabriele; Deringer, Volker L.; van Wüllen, Leo; Gasteiger, Hubert A.; Fässler, Thomas F.
Abstract: Solid electrolyte materials are crucial for the development of high‐energy‐density all‐solid‐state batteries (ASSB) using a nonflammable electrolyte. In order to retain a low lithium‐ion transfer resistance, fast lithium ion conducting solid electrolytes are required. We report on the novel superionic conductor Li9 AlP4 which is easily synthesised from the elements via ball‐milling and subsequent annealing at moderate temperatures and which is characterized by single‐crystal and powder X‐ray diffraction. This representative of the novel compound class of lithium phosphidoaluminates has, as an undoped material, a remarkable fast ionic conductivity of 3 mS cm −1 and a low activation energy of 29 kJ mol −1 as determined by impedance spectroscopy. Temperature‐dependent 7 Li NMR spectroscopy supports the fast lithium motion. In addition, Li9 AlP4 combines a very high lithium content with a very low theoretical density of 1.703 g cm −3 . The distribution of the Li atoms over the diverse crystallographic positions between the [AlP4 ] 9− tetrahedra is analyzed by means of DFT calculations. Abstract : Lightweight and with fast lithium ion conduction : Solid electrolytes with a fast ion conduction are crucial for all‐solid‐state batteries. The new material Li9 AlP4 combines a high lithium content and a high ionic mobility of 3 mS cm −1 at 25 °C with a very low theoretical density of 1.703 g cm −3 .